ANALISIS CEMARAN BAKTERI Coliform DAN IDENTIFIKASI Escherichia coli PADA ES BATU BALOK DI KOTA KARAWANG - Himyatul Hidayah; Iin Lidia Putama Mursal; Hawa Ayu Susaningsih; Surya Amal (Pharma Xplore : Jurnal Sains dan Ilmu Farmasi, 2022)
Ice cubes are one of the food products that are well known by the public and are considered safe for consumption. The Aim of this research is to see the contamination of Coliform bacteria and the presence of Escherichia coli in ice cubes. Test methods used include: Coliform test and identification of Escherichia coli bacteria. The results showed that 2 of the 6 positive samples contained Coliform bacteria and Escherichia coli bacteria with MPN values ​​above the safe limit. The conclusion of this study is that the ice cubes used by the perpetrators around the city of Karawang have microbiological quality that is not suitable for consumption by the public and does not comply with the microbiological quality requirements of the Indonesian National Standard 01-3839-1996 regarding ice cubes, namely the Total Coliform Bacteria exceeds 0/ 100mL.